1998
DOI: 10.1007/s004230050109
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography with F-18-deoxyglucose in patients with differentiated thyroid carcinoma, elevated thyroglobulin levels, and negative iodine scans

Abstract: Introduction: In patients with differentiated thyroid carcinoma, elevated serum levels of thyroglobulin (hTg) may occur in spite of otherwise negative diagnostic procedures and in particular in spite of a negative iodine-131 scan. Positron emission tomography with F-18-deoxyglucose (FDG-PET) is a potentially useful method for the detection of metastatic lesions or the recurrence of thyroid cancer. We aimed to investigate whether FDG-PET is capable of detecting metastastic lesions or recurrence in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 17 publications
(12 reference statements)
1
26
0
3
Order By: Relevance
“…We rather focused on the clinical usefulness of a widely accepted method in the real clinical practice. According to the published data and our own analysis, a positive FDG-PET result was achieved in DTC patients with higher serum Tg level (18,22). When Tg cut-off level that constitutes an indication for FDG-PET is lower, the sensitivity of FDG-PET decreases as a larger tumor volume is related to the higher Tg level and simultaneously the larger tumor is easier to detect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We rather focused on the clinical usefulness of a widely accepted method in the real clinical practice. According to the published data and our own analysis, a positive FDG-PET result was achieved in DTC patients with higher serum Tg level (18,22). When Tg cut-off level that constitutes an indication for FDG-PET is lower, the sensitivity of FDG-PET decreases as a larger tumor volume is related to the higher Tg level and simultaneously the larger tumor is easier to detect.…”
Section: Discussionmentioning
confidence: 97%
“…PET combined with computed tomography (PET/ CT hybrid scanner Philips GEMINI GXL) was performed 60 min after intravenous administration of 7.4 mCi of 18 flourodeoxyglucose ( 18 FDG). The scanning volume covered the area from the top of the skull to the middle of the thighs.…”
Section: Methodsmentioning
confidence: 99%
“…We regard whole-body fluorine-18 fluorodeoxyglucose positron emission tomography (FDG PET) as essential in the diagnostic work-up of patients with elevated hTG and/or suspicious lesions without demonstrable 131 I uptake [6]. Using FDG PET, Alnafisi et al were able to identify metastatic lesions in the neck or upper mediastinum in 11/11 asymptomatic patients with positive hTG (median 61 ng/dl; range 25-12,000 under TSH stimulation), negative 131 I whole-body scans (3.7-7.4 GBq) and negative morphological imaging (cervical ultrasound and computed tomography of the neck and chest).…”
Section: Therapeutic Options In the Absence Of Iodine Uptakementioning
confidence: 99%
“…Thyroid cancers with remaining functional differentiation for hormone synthesis and iodine uptake appear to have low glucose metabolism whereas undifferentiated tumors show high glucose utilization [45]. Accordingly, FDG-PET studies have been found to allow detection of metastases in patients with rising thyreoglobulin levels and normal iodine-131 scintigraphy [7,55]. Medullary thyroid carcinoma has also been found to show increased FDG uptake.…”
Section: Tumors Of the Endocrine Glands And Neuroendocrine Tumorsmentioning
confidence: 99%